Conceptual Design of an Integrated Smart Home System with PV Solar Power for Traditional Minahasa Wooden House - Tulangi, Gideon F.; Rumokoy, Stieven Netanel; Atmaja, I Gede Para; Pangemanan, Daisy D. G.; Dodie, Stanley B.; Langie, Maureen B. (CCIT (Creative Communication and Innovative Technology) Journal, 2025)
The traditional Minahasa wooden house is an integral part of Indonesia's cultural heritage. However, in this modern era, the challenge of preserving cultural authenticity while introducing it to the technological era is becoming increasingly urgent. This research aims to design a Smart Home System concept integrated with Photovoltaic (PV) Solar Power Plant for traditional Minahasa wooden houses. The objective of this study is to identify the potential for integrating smart home technology and PV Solar Power Plant in Minahasa wooden houses and to develop a concept that combines traditional elements with modern technology. The research methodology will involve a literature review to understand the concepts of smart homes, PV Solar Power Plant, and the characteristics of traditional Minahasa wooden houses. Additionally, descriptive research through interviews will be conducted in collaboration with industry partners to obtain data and examples of traditional Minahasa wooden houses to be used as benchmarks in the concept design. This research can contribute to integrating modern technology into Indonesia's cultural traditions while enhancing the competitiveness of Minahasa wooden house products in the market. The result of this research is a conceptual design for the implementation of a Smart Home System integrated with a PV rooftop solar power plant system in Minahasa wooden houses. The utilization of solar energy as electrical energy is predicted to achieve an annual energy yield of 16,775 kWh.